Pengelolaan Gangguan Persepsi Sensori: Halusinasi Pendengaran Dengan Severe Depressive Episode With Psychotic Symptoms : Management of Sensory Perception Disorders: Auditory Hallucinations With Severe Depressive Episode With Psychotic Symptoms - ANNISA AZIZAH; Ana Puji Astuti (Journal of Holistics and Health Sciences (JHHS), 2022)
Sensory perception disorder is a condition that occurs in a person who experiences changes in the shape and number of stimuli that come from outside, resulting in a sensory perception disorder: hallucinations. One of the sensory perception disorders is auditory hallucinations, where the patient will experience changes in perception and often hear false or unreal whispers and have no form. The purpose of writing this scientific paper is to describe the management of sensory perception disorders: auditory hallucinations with severe depressive episodes with psychotic symptoms at Wisma Drupad RSJ Prof. Dr. Soerojo Magelang. This type of research uses a descriptive method with the approach used, namely the nursing care approach including nursing diagnoses, nursing interventions, nursing implementation and nursing evaluations. The data obtained from the perception assessment that the patient said he heard a whisper, usually appeared when the patient was alone or doing activities. The patient is confused, daydreaming, pacing, the patient is disturbed and uncomfortable with whispering sounds. Whispers are not clear but real audible. Whispers were frequent and countless. So that a nursing diagnosis of Daignosis disorder was established which was enforced by sensory perception disorders: auditory hallucinations. The interventions arranged were teaching SP 1 how to rebuke hallucinations, SP 2 with 5 correctly taking medication, SP 3 controlling hallucinations by talking and SP 4 controlling hallucinations by doing favorite activities or positive activities. Furthermore, the implementation of SP1, SP2 and SP3 and an evaluation is carried out at the end of management. Based on the results of nursing management, it can be concluded that the problem of sensory perception disorders: auditory hallucinations is partially resolved by reducing the frequency of hallucinations. ABSTRAK Gangguan persepsi sensori adalah suatu keadaan yang terjadi dalam diri seseorang yang mengalami perubahan bentuk dan jumlah rangsangan yang datang dari luar sehingga mengakibatkan terjadinya gangguan persepsi sensori: halusinasi. Salah satu gangguan persepsi sensori yaitu halusinasi pendengaran, dimana pasien akan mengalami adanya perubahan pada persepsi dan sering mendengar suara bisikan palsu atau tidak nyata dan tidak ada wujudnya. Tujuan dari penulisan Karya Tulis Ilmiah ini untuk menggambarkan pengelolaan gangguan persepsi sensori: halusinasi pendengaran dengan severe depressive episode with psychotic symptoms di Wisma Drupada RSJ Prof. Dr. Soerojo Magelang. Jenis penelitian ini menggunakan metode deskriptif dengan pendekatan yang digunakan yaitu pendekatan asuhan keperawatan meliputi diagnosis keperawatan, intervensi keperawatan, implementasi keperawatan dan evaluasi keperawatan. Diperoleh data dari pengkajian persepsi bahwa pasien mengatakan mendengar suara bisikan, biasanya muncul saat pasien sedang sendiri atau beraktifitas. Pasien bingung, melamun, mondar-mandir, pasien terganggu dan tidak nyaman dengan suara bisikan. Suara bisikan tidak jelas tapi nyata terdengar. Suara bisikan sering muncul dan tidak terhitung. Sehingga ditegakkan diagnosis keperawatan gangguan Diagnosis yang ditegakkan gangguan persepsi sensori: halusinasi pendengaran. Intervensi yang disusun yaitu ajarkan SP 1 cara menghardik halusinasi, SP 2 dengan 5benar minum obat, SP 3 kontrol halusinasi dengan bercakap-cakap dan SP 4 kontrol halusinasi dengan melakukan kegiatan yang disukai atau kegiatan positif. Selanjutnya implementasi dari SP1, SP2 dan SP3 dan dilakukan evaluasi di akhir pengelolaan. Berdasarkan dari hasil pengelolaan keperawatan, maka dapat disimpulkan masalah gangguan persepsi sensori: halusinasi pendengaran teratasi sebagian dengan berkurangnya frekuensi munculnya halusinasi.